2012
DOI: 10.1021/am3001677
|View full text |Cite
|
Sign up to set email alerts
|

Plastic-Syringe Induced Silicone Contamination in Organic Photovoltaic Fabrication: Implications for Small-Volume Additives

Abstract: Herein, the implications of silicone contamination found in solution-processed conjugated polymer solar cells are explored. Similar to a previous work based on molecular cells, we find this contamination as a result of the use of plastic syringes during fabrication. However, in contrast to the molecular case, we find that glass-syringe fabricated devices give superior performance than plastic-syringe fabricated devices in poly(3-hexylthiophene)-based cells. We find that the unintentional silicone addition alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…30 nm poly(ethylenedioxythiophene): poly(styrenesulfonic acid) (HC Stark) film was spincoated onto the treated substrates and the casted films were annealed at 120 C for 10 min. The blend solutions were then filtered via plastic-syringe (note, this is known to affect the solution's wettability) 46 and a 0.22 lm PTFE filter (Sigma-Aldrich). The active layer was then spun at 400 to 600 rpm for 60 s onto the PEDOT covered substrates and slow-dried in a Petri dish.…”
Section: Methodsmentioning
confidence: 99%
“…30 nm poly(ethylenedioxythiophene): poly(styrenesulfonic acid) (HC Stark) film was spincoated onto the treated substrates and the casted films were annealed at 120 C for 10 min. The blend solutions were then filtered via plastic-syringe (note, this is known to affect the solution's wettability) 46 and a 0.22 lm PTFE filter (Sigma-Aldrich). The active layer was then spun at 400 to 600 rpm for 60 s onto the PEDOT covered substrates and slow-dried in a Petri dish.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, PDMS more likely operates as nucleation agent. As a common lubricant, PDMS contamination may factor into the performance variability of solution‐processed BHJ OPVs deposited from plastic syringes …”
Section: A Brief History Of Solvent Additives In Organic Photovoltaicsmentioning
confidence: 99%
“…Investigating the literature revealed that a variety of contamination sources could possibly play a role. These sources include, but are not limited to: glue from the adhesive tape used for cleaving HOPG 50 , poor quality solvents 51 , plastic syringes 52,53 , flexible tubes, and air quality. Also, when employing the ethanol-exchange to nucleate nanobubbles a lot of care has to be taken as ethanol is especially susceptible to distribute any organic contaminants present in the nucleation procedure.…”
Section: A) B)mentioning
confidence: 99%